1996
DOI: 10.1002/etc.5620150409
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cd and Cu in anaerobic estuarine sediments. II. Bioavailability, body burdens and respiration effects as related to geochemical partitioning

Abstract: Abstract-The relationship between Cd and Cu distribution in sediment geochemical fractions and their bioavailability was studied. A fine-sandy textured estuarine sediment was treated with all combinations of 0, 2.5, and 5 mg/kg Cd and 0, 12, and 25 mg/kg Cu using the chloride salts of each metal. Grass shrimp (Palaemonetes pugio), blue mussel (Mytilus edulis), and hard clam (Mercenaria mercenaria) were exposed to the treated sediments in aquaria with 20 ppt artificial seawater for 14 d. Sediments were sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 15 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This study demonstrated that in sediments having excess sulfide, added Cu resulted in the liberation of Cd into more biologically available geochemical phases and increased the extractability of the Cd in the OSP, the largest reservoir for Cd. As shown in part II of this paper [25], biological uptake of the metals, especially Cd, is increased by this shift in geochemical phase distribution.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This study demonstrated that in sediments having excess sulfide, added Cu resulted in the liberation of Cd into more biologically available geochemical phases and increased the extractability of the Cd in the OSP, the largest reservoir for Cd. As shown in part II of this paper [25], biological uptake of the metals, especially Cd, is increased by this shift in geochemical phase distribution.…”
Section: Resultsmentioning
confidence: 91%
“…The time component of the interactions signified that the majority of both metals precipitated or were sorbed rapidly into the OSP upon their addition to the sediments and over the next few days, geochemical reactions occurred that caused the phase shifts. These reactions must have occurred in a relatively short time because biological responses to interactions also took place (see part II; reference [25]). Other facts indicate that metal distribution stability was reached within a short (hours or few days) time: (1) the sediments were thoroughly mixed after metal addition and equilibrated before the bioassay was started and (2) there was no change in phase distribution of the 0 treatment from before the spiking process until the end of the bioassay.…”
Section: Resultsmentioning
confidence: 99%
“…Although extensive literature exists for metal toxicity to embryonic, larval [8][9][10][11], and adult bivalves [12][13][14], there is little recent literature relevant to larval M. mercenaria and copper toxicity [15][16][17]. One of the most frequently cited references, Calabrese et al [16], reported values of the lowest concentration at which 5% of the organisms died (LC5), at which 50% died (LC50), and at which 95% died (LC95) of 4.9, 16, and 28 g/L, respectively, for 2-d-old larval clams exposed to varying copper concentrations in a static renewal dosing scheme [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive literature exists for metal toxicity to embryonic, larval [8–11], and adult bivalves [12–14], there is little recent literature relevant to larval M. mercenaria and copper toxicity [15–17]. One of the most frequently cited references, Calabrese et al [16], reported values of the lowest concentration at which 5% of the organisms died (LC5), at which 50% died (LC50), and at which 95% died (LC95) of 4.9, 16, and 28 μg/L, respectively, for 2‐d‐old larval clams exposed to varying copper concentrations in a static renewal dosing scheme [16,17].…”
Section: Introductionmentioning
confidence: 99%